2018
DOI: 10.2337/dc18-0802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Visit-to-Visit Fasting Plasma Glucose Variability on the Development of Type 2 Diabetes: A Nationwide Population-Based Cohort Study

Abstract: OBJECTIVEAlthough increasing evidence suggests the association between short-term variability of fasting plasma glucose (FPG) and diabetic complications or mortality, the impact of visit-to-visit variability of FPG on the development of type 2 diabetes (T2D) has not been evaluated. RESEARCH DESIGN AND METHODSOur analysis included 131,744 Korean men and women without diabetes using the Korean National Health Insurance System cohort with periodic health examination program. FPG variability was calculated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…The meaning of increased GGT variability is not yet clear. Several recent publications have considered the role of fluctuations in blood glucose, blood pressure, lipid, and body weight on the development of diabetes, CVD, and early death regardless of baseline variables 13,37 . Some basic research data indicate that fluctuations in blood glucose and blood pressure can increase oxidative stress more than continuous hyperglycemia or hypertension 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of increased GGT variability is not yet clear. Several recent publications have considered the role of fluctuations in blood glucose, blood pressure, lipid, and body weight on the development of diabetes, CVD, and early death regardless of baseline variables 13,37 . Some basic research data indicate that fluctuations in blood glucose and blood pressure can increase oxidative stress more than continuous hyperglycemia or hypertension 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have investigated the prognostic significance of glucose variability in individuals without diabetes. Recently, visit-to-visit fasting glucose variability has been reported as a risk factor for the development of type 2 diabetes [80]. We recently showed that high variability of FBG was an independent predictor of mortality and CV events among the general population [68].…”
Section: Glucose Variabilitymentioning
confidence: 91%
“…Visit-to-visit variability in FBG and HbA1c was associated with the risks of microvascular and macrovascular events and all-cause mortality among patients with type 2 diabetes using data from the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial [80]. Variability in FBG over the course of >7.5 years of follow-up was a potent predictor of ischemic stroke in 28,534 patients with type 2 diabetes in the Taiwan Diabetes Study [81].…”
Section: Glucose Variabilitymentioning
confidence: 99%
“…The study was performed on 234,427 subjects, all of whom were tested for COVID-19 with diagnosis codes of B342, B972, Z208, Z290, U18, U181, Z038, Z115, U071, and U072. The main study [14,15] or heart failure (I11.0, I13.0, I13.2, I50.0, I50.1, I50.9) [16] with at least one annual claim for prescription of an antihypertensive drug. A total of 62,909 subjects aged ≥ 19 years were analyzed.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%